Impact of vacuum stability, perturbativity and XENON1T on global fits of $$\mathbb {Z}_2$$ Z2 and $$\mathbb {Z}_3$$ Z3 scalar singlet dark matter - Peter Athron; Jonathan M. Cornell; Felix Kahlhoefer; James McKay; Pat Scott; Sebastian Wild (European Physical Journal C: Particles and Fields, 2018)
Abstract Scalar singlet dark matter is one of the simplest and most predictive realisations of the WIMP (weakly-interacting massive particle) idea. Although the model is constrained from all directions by the latest experimental data, it still has viable regions of parameter space. Another compelling aspect of scalar singlets is their ability to stabilise the electroweak vacuum. Indeed, models of scalar dark matter are not low-energy effective theories, but can be valid all the way to the Planck scale. Using the GAMBIT framework, we present the first global fit to include both the low-energy experimental constraints and the theoretical constraints from UV physics, considering models with a scalar singlet charged under either a $$\mathbb {Z}_2$$ Z2 or a $$\mathbb {Z}_3$$ Z3 symmetry. We show that if the model is to satisfy all experimental constraints, completely stabilise the electroweak vacuum up to high scales, and also remain perturbative to those scales, one is driven to a relatively small region of parameter space. This region has a Higgs-portal coupling slightly less than 1, a dark matter mass of 1–2 TeV and a spin-independent nuclear scattering cross-section around $$10^{-45}\,\hbox {cm}^2$$ 10-45cm2 .